2003
DOI: 10.1023/a:1022851324044
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and pharmacological interventions for child crime victims

Abstract: Children may develop a variety of difficulties following victimization, including posttraumatic stress disorder (PTSD), other anxiety symptoms, depressive disorders, externalizing symptoms, or substance use disorders. Some children appear to be resilient in the face of victimization and do not report significant difficulties. A growing number of treatment studies for child abuse victims has supported the efficacy of trauma-focused cognitive-behavioral therapy (CBT); however, more research is needed to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 72 publications
1
13
0
1
Order By: Relevance
“…Minimum and maximum scores are 3 and 12 respectively. This variable was included as a measure of respondents’ sense of safety in their current environments which if low can represent the potential for further traumatization, ongoing anxiety and other symptoms which may lead to help seeking (Cohen, Berliner, & Mannarino, 2003; Elliot, Quinless, & Parietti, 2000; Kessler, 2000). …”
Section: Methodsmentioning
confidence: 99%
“…Minimum and maximum scores are 3 and 12 respectively. This variable was included as a measure of respondents’ sense of safety in their current environments which if low can represent the potential for further traumatization, ongoing anxiety and other symptoms which may lead to help seeking (Cohen, Berliner, & Mannarino, 2003; Elliot, Quinless, & Parietti, 2000; Kessler, 2000). …”
Section: Methodsmentioning
confidence: 99%
“…A growing number of studies of child abuse victims have supported the effectiveness of trauma-focused CBT 80. A review article found that promising treatments for war-related PTSD in refugee children and adolescents include CBT, testimonial psychotherapy, narrative exposure therapy, and EMDR 81.…”
Section: Cbt For Ptsd In Children and Adolescentsmentioning
confidence: 99%
“…Similar to the mentioned publications, earlier reviews essentially address the lack of definitive studies on psychopharmacotherapy for PTSD [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], the drawbacks in study designs [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], also in comorbid conditions [30] and among specific populations, such as crime victims [39] as well as the need for head-to-head trials for the different treatment modalities [26].…”
Section: Reviews On Psychopharmacotherapy Of Ptsd Among Children and mentioning
confidence: 99%